FAKTOR-FAKTOR PENGHAMBAT GURU DALAM PELAKSANAAN PEMBELAJARAN BERDASARAKAN KURIKULUM 2013 DI SDN 002 TEBING - Tisrin Maulina Dewi; Fitria Meilina; Tri Wahyuni; Desi Indriyani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Lack of learning training based on the 2013 curriculum for teachers results in a lack of ability and understanding of teachers in preparing learning tools. And the number of each class being taught. The purpose of this study is to determine the factors inhibiting teachers in implementing laerning based on the 2013 curriculum at sdn 002 Tebing Kabupaten Karimun. This research is a quantitative descriptive research. The population in this study were all teacher assemblies up to sdn 002 Tebing Kabupaten Karimun district. The sample was selected using a total sampling technique that involved all 17 teachers from sdn 002 Tebing. Data collection techniques were carried out by questionnaire documentation and interviews. The data analysis technique used is descriptive quantitative approach. Based on the results of the study, it is known that the teacher experiences obstacles, seen from the constuctivism indicator, it is classifiedin the sufficient category, namely by the number of achievement levels of respondents (72.65). Of the indicators asked are classified in the sufficient category, namely by the number of achievement levels of respondents (75.49). Of the indicators of cooperation are classified in the sufficient category, namely by number of achievement levels of he respondents (65.44). Of the modeling indicators are classified in the sufficient category, namely by the number of achievement levels of the respondents (68.14). Of the reflection indicators classified in the sufficient category, namely by the number of aachievement levels of respondents (77.94). Of the authentic assessment indicators are classified in the sufficient category, namely by the number of respondents achievement levels (75.37). Kata Kunci: Faktor Penghambat, Proses Pembelajaran,dan Kurikulum 2013.